Case report: Levodopa-responsive parkinsonism with akinetic mutism after ventriculo-peritoneal shunt - Zhang, Ying; Li, Ping; Zhang, Jifeng; Li, Chunyang; Sun, Peng; Li, Fujun; Jiao, Zhuomin (Frontiers in Neurology, 2023)
Background: Parkinsonism and akinetic mutism (AM) following ventriculo-peritoneal shunt (VPS) without underdrainage used to be considered rare, but may be underdiagnosed in daily clinical practice. Although the pathophysiology is still unclear, in several case reports, the parkinsonism and AM after VPS shows responsiveness to dopaminergic treatment. Case Presentation: We report a 19-year-old male that presented with severe parkinsonism and AM after VPS. Meanwhile, 18F-FDG-PET showed a cortical and subcortical hypometabolism. Fortunately, levodopa dramatically improved patient's symptoms and brain hypometabolism. This report provides support for the possibility that dopamine deficiency inhibits brain metabolism, and further elucidates the pathogenesis of parkinsonism and AM. Conclusion: This report highlights the presentation of a treatable parkinsonism and points out that Levodopa and/or dopamine agonist should be the first choice if the patients develop parkinson-like symptoms after VPS.